Extracellular Matrix Stiffness: New Areas Affecting Cell Metabolism - Ge, Heming; Tian, Mengxiang; Pei, Qian; Tan, Fengbo; Pei, Haiping (Frontiers in Oncology, 2021)
In recent years, in-depth studies have shown that extracellular matrix stiffness plays an important role in cell growth, proliferation, migration, immunity, malignant transformation, and apoptosis. Most of these processes entail metabolic reprogramming of cells. However, the exact mechanism through which extracellular matrix stiffness leads to metabolic reprogramming remains unclear. Insights regarding the relationship between extracellular matrix stiffness and metabolism could help unravel novel therapeutic targets and guide development of clinical approaches against a myriad of diseases. This review provides an overview of different pathways of extracellular matrix stiffness involved in regulating glucose , lipid and amino acid metabolism.